Intercultural Communication in the Work of a Translator - Shokhsanam Mukhtorbekqizi Bekmuratova (Journal of Higher Education and Academic Advancement, 2024)
This article analyzes the process of identifying and comprehensively studying the cultural factors influencing the translation process. It is necessary to study the phenomenon of translation in the aspect of intercultural communication, including the study of cultural determinism of the translator.